Thiocyanate- and thiol-functionalized p-doped quantum dot colloids for the development of bulk homojunction solar cells - Dambhare, V. Neha; Sharma, Ashish; Mahajan, Chandan; Rath, Arup K. (Energy Technology, 2022)
Progress in device engineering and surface passivation strategies has led to steady progress in colloidal quantum dot (QD) solar cells. Bulk homojunction (BHJ) device architecture has several advantages over the conventional planar junction in developing QD solar cells. Herein, surface ligand chemistry is utilized to control the doping type and dispersibility of oppositely doped PbS QDs to develop BHJ solar cells. Thiocyanate and thiol ligand combination is introduced to develop p-PbS QD ink, which is blended with halide-passivated n-PbS QDs to build BHJ solar cells. It is shown that BHJ solar cells are benefited from high energy offset and higher hole mobility. This leads to the superior carrier extraction from a thicker active layer without compromising fill factor and open circuit voltage. Power conversion efficiency has reached 10.7% in 530 nm-thick BHJ solar cells, a 24% improvement over the best performing planar solar cells. With the help of the 1D solar cell capacitance simulator, it is shown that a 15% efficient QD solar cell can be realized by further improving the hole mobility above 0.1 cm(2) V-1 s(-1).
Keywords: bulk homojunctions; Doping; quantum dots; solar cells; surface functionalization

Multi-bandgap quantum dots ensemble for near-infrared photovoltaics - Mahajan, Chandan; Dambhare, Neha V.; Biswas, Arindam; Sharma, Anjali; Shinde, Dipak Dattatray; Rath, Arup K. (Energy Technology, 2023)
Narrow bandgap quantum dots (QDs) are an important class of materials for near-infrared (NIR) optoelectronic devices owing to their size-tunable bandgap and chemical root processing. In photovoltaic applications, NIR QDs could be particularly useful to complement the sub-bandgap transmission loss of NIR solar radiation from perovskite and c-Si solar cells. However, insufficient carrier extraction thickness associated with the narrow NIR excitonic bandwidth of QDs limits the conversion efficacy of the broad NIR solar spectrum. Here, we utilize a multi-bandgap QD ensemble which widens the NIR absorption bandwidth to mimic the broad solar spectrum. A solution-phase ligand passivation strategy is used to control doping properties and energy level alignment of multi-bandgap QDs. We successfully developed bulk-heterojunction solar cells using the multi-bandgap QD ensemble, which yields higher carrier extraction thickness and broader NIR absorption. The gain from NIR absorption and carrier transport resulted in higher short-circuit current generation and power conversion efficiency (PCE) in solar cell devices. The champion device shows 8.73% PCE under 1.5 AM solar illumination and 7.44% and 5.05% PCE for the NIR photons transmitted from perovskite and c-Si layers.
Keywords: bulk-heterojunctions; multi-bandgap; near-infrared; quantum dots; solar cells; surface passivation

Scanning tunneling microscopy investigation of synaptic behavior in AgInS2 quantum dots: effect of ion transport in neuromorphic applications - Betal, Atanu; Chetia, Anupam; Bera, Jayanta; Saikia, Dibyajyoti; Sharma, Ashish; Rath, Arup K.; Sahu, Satyajit (ACS Applied Nano Materials, 2024)
Scanning tunneling microscopy (STM) is a powerful technique for investigating the nanoscale properties of functional materials. Additionally, scanning tunneling spectroscopy (STS) facilitates the determination of the local density of states (LDOS) within the material. In this study, we present an exploration of the resistive switching (RS) properties and neuromorphic computing capabilities of individual AgInS2 quantum dots, utilizing STM and STS techniques. By examining the material's bandgap and its temperature dependence, we uncover a nonlinear variation below the Debye temperature and a linear trend at higher temperatures. Moreover, STS measurements demonstrate changes in the conducting states induced by localized pulses, further confirming the unique characteristics of the quantum dots. The experimental devices constructed by using these quantum dots effectively replicate the RS properties observed at the nanoscale. To assess the neuromorphic application of the devices, pulse transient measurements simulating the learning and forgetting processes were conducted. The gradual set and reset processes successfully mimic the information retention and erasure capabilities essential for neuromorphic computing. Notably, the resistive switching mechanism in these devices is attributed to localized ionic transport, which highlights the significant involvement of ionic species in the observed RS behavior. The outcomes of this study contribute to the fundamental understanding of RS properties in single AgInS2 quantum dots and offer valuable insights into their potential applications in neuromorphic computing.
Keywords: corona poling; Ion transport; neuromorphic computing; quantum dots; resistive switching; Scanning tunneling microscopy; STS

Synthesis and processing strategy for high-bandgap PbS quantum dots: a promising candidate for harvesting high-energy photons in solar cells - Shinde, Dipak Dattatray; Sharma, Anjali; Dambhare, Neha V.; Mahajan, Chandan; Biswas, Arindam; Mitra, Anurag; Rath, Arup K. (ACS Applied Materials & Interfaces, 2024)
The wide tunability of the energy bandgap of colloidal lead sulfide (PbS) quantum dots (QDs) has uniquely positioned them for the development of single junction and tandem solar cells. While there have been substantial advancements in moderate and narrow bandgap PbS QDs-ideal for single junction solar cells and the bottom cell in tandem solar cells, respectively; progress has been limited in high-bandgap PbS QDs that are ideally suited for the formation of the top cell in tandem solar cells. The development of appropriate high bandgap PbS QDs would be a major advancement toward realizing efficient all-QD tandem solar cells utilizing different sizes of PbS QDs. Here, we report a comprehensive approach encompassing synthetic strategy, ligand engineering, and hole transport layer (HTL) modification to implement high-bandgap PbS QDs into solar cell devices. We achieved a greater degree of size homogeneity in high-bandgap PbS QDs through the use of a growth retarding agent and a partial passivation strategy. By adjusting the ligand polarity, we successfully grow HTL over the QD film to fabricate solar cells. With the aid of an interface modifying layer, we incorporated an organic HTL for the realization of high-performance solar cells. These solar cells exhibited an impressive open-circuit voltage of 0.824 V and a power conversion efficiency of 10.7%, marking a 360% improvement over previous results.
Keywords: charge transport; lead sulfide; ligand passivation; quantum dots; solar cell

Synergistic improvement of narrow bandgap PbS quantum dot solar cells through surface ligand engineering, near-infrared spectral matching, and enhanced electrode transparency - Sharma, Anjali; Shinde, Dipak Dattatray; Mahajan, Chandan; Dambhare, Neha V.; Biswas, Arindam; Mitra, Anurag; Girade, Vrushali S.; Rath, Arup K. (ACS Applied Materials & Interfaces, 2025)
The tunability of the energy bandgap in the near-infrared (NIR) range uniquely positions colloidal lead sulfide (PbS) quantum dots (QDs) as a versatile material to enhance the performance of existing perovskite and silicon solar cells in tandem architectures. The desired narrow bandgap (NBG) PbS QDs exhibit polar (111) and nonpolar (100) terminal facets, making effective surface passivation through ligand engineering highly challenging. Despite recent breakthroughs in surface ligand engineering, NBG PbS QDs suffer from uncontrolled agglomeration in solid films, leading to increased energy disorder and trap formation. The limited NIR transparency of commonly used indium-doped tin oxide (ITO) electrodes and inadequate NIR radiation from commercially available solar simulators further compromise the true performance of NBG PbS QDs in solar cells. Here, we employ a hybrid ligand strategy based on inorganic cadmium halide and organic thiol molecules, leading to the partial substitution of surface Pb atoms with Cd heteroatoms. This hybrid ligand strategy substantially reduces undesired QD fusion in solid films, improving the photophysical and electronic properties. By modulating the thickness of the ITO layer and managing refraction loss through a ZnO layer coating, we improved NIR transparency to above 80%. We combine an NIR light source with a solar simulator to achieve near-ideal spectral matching for a broader range with standard AM1.5G illumination. Enhancements in surface passivation of QDs, improvements in NIR transparency of electrodes, and a spectral matched light source setup help us achieve solar cell power conversion efficiencies of 12.4%, 4.48%, and 1.37% under AM 1.5G, perovskite filter, and silicon filter illuminations, respectively. A record open-circuit voltage (V oc) of 0.54 V and short-circuit current density (J sc) of 38.5 mA/cm2 are achieved under AM 1.5G illumination. We attribute these advancements in photovoltaic parameters to the reduction in Urbach tail states and intermediate trap density originating from superior surface passivation of QDs.
Keywords: lead sulfide; ligand passivation; near-infrared; quantum dots; solar cell; tandem solarcell